2016
DOI: 10.1111/dmcn.13151
|View full text |Cite
|
Sign up to set email alerts
|

Auditory brainstem maturation in normal‐hearing infants born preterm: a meta‐analysis

Abstract: The delayed conduction time towards and into the auditory brainstem at term age suggests atypical maturation of the brainstem in normal-hearing infants born preterm. Both the duration of gestation and the consequences of the preterm birth (intensive care needed) negatively affect maturation of the auditory brainstem, which may influence later development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 37 publications
2
36
1
5
Order By: Relevance
“…However, perinatal variables associated to prematurity could have influenced the maturation of the central auditory pathway as previously reported (Stipdonk et al, 2016). Finally, in the current study we did not consider the possible influence of gray matter maturation on auditory processes' development, which is known to show rapid growth during the first postnatal year (Gilmore et al, 2012) coinciding with a rapid postnatal development of dendritic trees, dendritic branching, spines and synapsis (Elston & Fujita, 2014).…”
Section: Figurementioning
confidence: 79%
“…However, perinatal variables associated to prematurity could have influenced the maturation of the central auditory pathway as previously reported (Stipdonk et al, 2016). Finally, in the current study we did not consider the possible influence of gray matter maturation on auditory processes' development, which is known to show rapid growth during the first postnatal year (Gilmore et al, 2012) coinciding with a rapid postnatal development of dendritic trees, dendritic branching, spines and synapsis (Elston & Fujita, 2014).…”
Section: Figurementioning
confidence: 79%
“…Auditory enrichment facilitates the development of the auditory cortex and stimulates the progression of neural arborisation and synaptogenesis [2,3]. Evidence from several studies demonstrates that the preterm infant's ability to process cortical signals is a significant factor affecting the development of receptive and expressive language skills [4,5,50]. Notably, auditory learning skills improve with increasing gestational age [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, for infants born preterm (especially < 28 weeks) this development occurs in the abnormal environment of the neonatal unit, during a critical period of neural arborisation and synaptogenesis [3]. Significant delays have been found in auditory brainstem responses of preterm infants at a term-equivalent age, reflecting atypical brainstem maturation [4]. This is apparent even in preterm infants with normal brain ultrasound scans [5], which is believed to be attributable to exposure to the extrauterine environment [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, our moderator analyses do not represent the full complement of factors that may affect the association between ASD and ABRs. For example, preterm delivery is associated with longer ABR latencies relative to full-term counterparts who are matched according to either chronological or corrected age [Jiang & Li, 2015;Stipdonk, Weisglas-Kuperus et al, 2016] and preterm delivery is a welldescribed risk factor for ASD. However, only three studies here reported specific information regarding perinatal health; one excluded preterm children [Roth, Muchnik et al, 2012], one included preterm children [Miron, Roth et al, 2016], and one excluded children with "infective prenatal conditions" [Tas, Yagiz et al, 2007].…”
Section: Discussionmentioning
confidence: 99%